자동차 데이터 플랫폼: 교통사고 분석시스템의 연계방안 - 한효승(Hyo-Seung Han); 김중효(Joong-Hyo Kim); 김용환(Yong-Hwan Kim) (디지털콘텐츠학회논문지, 2024)
본 연구는 국내 자동차 산업 오픈플랫폼 생태계 구축사업 일환으로 추진되었으며, 자동차 산업 데이터 활용 및 활성화를 위한 기반(장비, 데이터 등)조성과 기업을 지원하는데 목적이 있다. 특히 자동차 산업에서 중요하게 활용되는 교통사고 데이터를 제공하는 교통사고 분석시스템과의 실시간 데이터 연계·연동상의 구조적인 문제점을 진단하고 운영 효율적인 측면의 해결 방안을 제시하고자 하였다. 또한 본 연구를 통하여 향후 자동차 산업 생태계에 사용자 요구를 위한 데이터 범용적 확장, 실시간 플랫폼과 시스템 간 서비스 제공 등을 통하여 자동차 부품, ICT 등 빅데이터 기반의 혁신을 유도하는데 기여하고자 한다. This study is part of South Korea’s initiative to establish an open platform ecosystem for the automotive industry. It aims to lay a foundation, including the necessary equipment and data, to enhance the utilization and activation of automotive industry data, thereby supporting businesses within the sector. The focus is on identifying and addressing structural problems concerning the real-time integration of the crucial traffic accident data provided by traffic accident analysis systems and proposing solutions to improve operational efficiency. This study also aims to expand the general utility of data to meet user demands, facilitate real-time services across platforms and systems, and drive innovation based on big data in areas such as automotive parts and ICT. Ultimately, the goal is to contribute to the development of a hybrid business model that integrates various industries within the automotive ecosystem. KCI Citation Count: 0